EKSISTENSI DAKWAH DALAM MERESPON PLURALISME - Ahmad Choirun Ulum; Muhammad Haramain; A. Nurkidam; Muh. Taufik (KOMUNIDA : Media Komunikasi dan Dakwah, 2017)
Da'wah delivered by the Holy Prophet, not only to the ahlul kitab, but to the plural society where he convey the religious message to the people in order to implement the Shari'ah of the religion correctly and responsibly following the guidance of the Qur'an and Hadith towards the creation of a peaceful, secure society , and affluent. The ongoing process makes every individual understand fully that dakwah is a duty with all responsibility and is accompanied by a consequence of obtaining God's approval. The nature of da'wah is not just to invite people to accept what a dai calls for, nor a person's intelligence in the pulpit or the ability to put ideas through writing. Moreover, da'wah is a horizontal relationship with each other that is interdependent. From here, there is another side that must be understood by those who carry out this missionary mandate, given that the duty and responsibility of a dai is a very big thing, let alone the activities of da'wah from time to time, from generation to generation, even from century to century, of course very varied, because will be found various challenges.